Enhancing wool dyeing with clove bud (Syzygium aromaticum) based natural dye via microwave treatment using a central composite design - ÖZOMAY, MERAL (My University, 2023)
This research investigates the viability of using Syzygium aromaticum (clove) as a natural dye for wool yarn through the application of microwave treatment and optimization using central composite design (CCD). As concerns grow over the environmental impact of synthetic dyes and their detrimental disposal in water bodies, the search for eco-friendly alternatives becomes imperative to revolutionize the textile industry. Microwave-assisted extraction of the colorant from clove powder is explored as an efficient and sustainable method, minimizing solvent usage and energy consumption compared to conventional techniques. To enhance colorfastness properties while eliminating the need for toxic mordants, green alternatives such as Al, Fe, and tannic acid, combined with plant phenolics from red sumac, pomegranate rind, and weld, are employed. According to the analysis of CCD, the higher color strength value 18.1653 was achieved using pH = 3, time = 50 min, temperature = 70 °C, and salt concentration = 1.5 g/100 mL. The optimized dyeing conditions also showed a maximum level of colorfastness properties of 5 for light, 5 for wash, 5 for dry rubbing, and 4 for wet rubbing. The findings from Fourier-transform infrared spectroscopy and scanning electron microscopy analyses provide valuable insights into the chemical and morphological changes induced by microwave treatment and dyeing with clove extract. The results affirm the presence of eugenol as a potential active molecule responsible for the captivating color of clove flower buds, validating its suitability as a natural dye source for wool. This study highlights the promising potential of microwave-assisted extraction and plant-based biomolecules as innovative and environmentally friendly approaches in natural dyeing, paving the way for a more sustainable future in the textile industry. Embracing these eco-friendly practices allows the textile sector to reduce its ecological footprint and contribute to a cleaner and greener environment. Further research and implementation of these techniques can foster a more harmonious coexistence with nature, ensuring a healthier ecosystem for all.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; central composite design; mordanting; natural dye; sustainability; Syzygium aromaticum (clove); Wool